MOBILE TRANSACTION SYSTEM BERBASIS ANDROID DENGAN METODE RESTFULL WEB SERVICE - Shindy Maharani; Elvira Asril (J-Com (Journal of Computer), 2023)
Abstract:CV. Laut Abadi Steel is a company engaged in the sale of building materials. The main goal is to improve the quality of service to customers in terms of buying and selling services. CV. Laut Abadi Steel has not yet used information technology so there are several problems with the transaction system because it is still done manually. Therefore, an Android-based mobile system is needed that is integrated into a restfull web service in order to increase efficiency in serving customers. Customers will find it easier to get information about the products offered, place orders, and arrange transactions online without having to visit a store. It can also speed up the transaction process and reduce communication errors between customers and stores. The use of restful web services in mobile applications also allows integration with other systems, such as payment systems that can improve customer experience. Thus, the results of testing the designed application work according to the system design mechanism at the beginning. This application can handle well the process of displaying building product information, managing payments, and printing sales reports and invoices.Keyword: mobile; transaction; restfull web service; android Abstrak: CV. Laut Abadi Steel merupakan perusahaan yang bergerak di bidang penjualan material bangunan. Tujuan utamanya adalah meningkatkan kualitas pelayanan kepada pelanggan dalam hal jasa jual beli. CV. Laut Abadi Steel belum menggunakan teknologi informasi sehingga terdapat beberapa kendala pada sistem transaksinya karena masih dilakukan secara manual. Oleh karena itu dibutuhkan sistem mobile berbasis android yang terintegrasi pada restfull web service agar dapat meningkatkan efisiensi dalam pelayanan kepada pelanggan. Pelanggan akan lebih mudah mendapatkan informasi tentang produk yang ditawarkan, melakukan pemesanan, dan mengatur transaksi secara online tanpa harus mengunjungi toko. Hal ini juga dapat mempercepat proses transaksi dan mengurangi kesalahan komunikasi antara pelanggan dan toko. Penggunaan restful web service dalam aplikasi mobile juga memungkinkan integrasi dengan sistem lain, seperti sistem pembayaran yang dapat meningkatkan pengalaman pelanggan. Dengan demikian, hasil pengujian aplikasi yang dirancang bekerja dengan sesuai mekanisme perancangan sistem di awal. Aplikasi ini dapat menangani dengan baik proses menampilkan informasi produk bangunan, pengelolaan pembayaran, dan cetak laporan penjualan serta invoice.Kata Kunci : mobile; transaksi; restfull web service; android